Islamic Patterns in Persian’s Herat School of Painting: A Study on Baysonghori Shahnameh - Zoghi, Neda; Mohd Nor, Mohd Roslan; Abdul Hamid, Faisal @ Ahmad Faisal (Online Journal of Research in Islamic Studies, 2018)
One of the characteristics of the Herat School is that it has continuously used various decorative motifs in painting. That is why in the present paper some samples from the Herat School have been selected and analysed to illustrate and explain the difference and superiority of the Herat School over other Persian painting schools. The paintings of Shahnameh-y-Baysonqori contain many decorative motifs such as plants, animals, geometrical motifs, decorations of inscriptions and other architectural elements with highly precise and detailed drawings and decorative patterns. The Persian painters in the Timurid dynasty have used Islamic patterns including arabesque and geometric motifs as decorations. Iranian painters used arabesque shapes to create movement, rhythm, emotion, and space to represent the beauty of objects inherent in the beauty of God.